The Effect of Expressive Writing Therapy to Improve Students' Public Speaking Ability in Front of the Class - Rochani; Raudah Zaimah Dalimunthe; Gagah Gilang Purnama (Department of Guidance and Counseling, FIP, Undiksha, 2022)
This research was conducted to assist students in improving their public speaking skills with group guidance services using expressive writing therapy techniques. This study uses a quantitative experimental method. The total population is 275 students with population characteristics aged 15-17 at SMAN 1 Baros. The sampling technique used purposive sampling and got 10 students who had a low level of public speaking ability which were then given treatment. The analysis technique used in testing the hypothesis is the Wilcoxon signed ranks test. The results of the study were seen from the implementation of the pre-test and post-test, there was a significant increase from the average value of 66.2 to 104.2. Analysis of the Wilcoxon signed ranks test on the hypothesis decision making process, the value of 0.005 is lower than 0.05, so it can be concluded that the hypothesis is declared accepted. Thus statistically it can be concluded that group counseling with expressive writing therapy techniques can influence students' public speaking skills.